2016
DOI: 10.1021/acs.jpcc.6b01015
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Stability of a Carbon Monoxide Monolayer Adsorbed on Platinum under Electrochemical Control Probed by Sum-Frequency Generation Spectroscopy

Abstract: We establish a new procedure to study the steady state adsorption of carbon monoxide (CO) at the surface of platinum under electrochemical control over a wide potential range in aqueous acidic solution. Using highly concentrated solutions of CO in perchloric acid medium enables the formation of a tightly packed and very stable CO monolayer at the surface of the metal, which allows cyclic voltammetry in the [-1200;+1500mV] potential range (vs Ag/AgCl). We use Sum-Frequency Generation (SFG) spectroscopy to show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…In our analysis of equation (3) for the case of a single-frequency system (n=1), we use ω 1 =2100 cm -1 , which is in the vicinity of nitrile or carbon monoxide systems reported in the literature [15][16][17][18][19] . With an arbitrary value of A 1 M 1 =10, a damping factor, Γ ν , of 15 cm -1 , γ 1 =0 degrees, and !…”
Section: Single Oscillatormentioning
confidence: 99%
“…In our analysis of equation (3) for the case of a single-frequency system (n=1), we use ω 1 =2100 cm -1 , which is in the vicinity of nitrile or carbon monoxide systems reported in the literature [15][16][17][18][19] . With an arbitrary value of A 1 M 1 =10, a damping factor, Γ ν , of 15 cm -1 , γ 1 =0 degrees, and !…”
Section: Single Oscillatormentioning
confidence: 99%
“…The SFG experimental setup used in the CLIO Free Electron Laser (FEL) European facility is described in detail elsewhere [49,54] [56] ranging from 5 to 150 mm delivers 10 ms long macropulses containing 2 ps micropulses (10 mJ per pulse, 2 cm À1 spectral resolution) and has the same repetition rate as the OPOs. The monitoring of the higher peak power delivered in the IR spectral range (7e8 mm in the present case) by the FEL with respect to the IR OPO allows working with sufficient energy reaching the surface electrode in a spectro-electrochemical cell designed for in situ SFG spectroscopy in aqueous electrolytes [49,55]. It is worth noting that in the present case we worked with deuterated water in order to be free from water absorption in the investigated IR spectral range.…”
Section: Sum Frequency Generation Spectroscopymentioning
confidence: 92%
“…SFG spectroscopy is a surface sensitive spectroscopy based on the nonlinear second order optical activity of materials (modelled by c (2) , the nonlinear second order susceptibility of the probed interface), depending on the Infrared and Raman activities of the molecules constituting the interfaces [54]. It is particularly wellsuited for the study of the electrochemical interface [55]. It follows the energy (u SFG ¼ u Vis þ u IR ) and momentum (ħk SFG ¼ ħk Vis þ ħk IR ) conservation rules.…”
Section: Sum Frequency Generation Spectroscopymentioning
confidence: 99%
“…53,54,56,57 Disentangling χ (2) ijk and χ (3) ijkz contributions to the vSFG response at charged interfaces is particularly challenging and has recently been the focus of several experimental and theoretical studies on model systems. 49,[53][54][55][56][57][58][59][60][61][62][67][68][69][70][71][72][73][74] Perhaps most importantly, these stud-ies have now revealed that the second-and third-order contributions to the SFG response from charged interfaces are not merely additive but instead modulated nonlinearly by the ionic strength-dependence of the χ (3) ijkz phase angle 59 and the phase interference 58,60 terms shown in Eq. 1.…”
Section: Vibrational Sum-frequency Generation Responsementioning
confidence: 99%